Synchronous Clear Cell Renal Carcinoma And Bilateral Invasive Duct Carcinoma Breast- Rare association - Badhe, Shreya Devidas; Padmanabhan, Anitha; Sawant, Kavita Prakash; Gadgil, Nitin M (Annals of Pathology and Laboratory Medicine, 2022)
Occurrence of multiple primary malignant tumors is very uncommon .Co occuring tumors can be synchronous or non synchronous.Tumors presenting within a period less than or equal to 6 months are called synchronous and if they occur after 6 months they are termed as metachronous. Synchronous malignancies are rarer than metachronous. For defining tumors as synchronous both the tumors should show criteria of malignancy, possibility of metastasis must have been ruled out and both the tumors should be pathologically distinct. Breast cancer is the commonest tumor to be associated with other malignancies such as colorectal, endometrial, ovarian carcinoma, yet occurrence of invasive ductal carcinoma with clear cell renal carcinoma is rare. We present a 70 year old female with synchronous Breast carcinoma and Renal clear cell carcinoma .